Accessibility and Tourist Satisfaction in Yogyakarta’s Museums: A User-Generated Content Analysis - Rizki Hardiana Shely; Amalia Permadi Vynska; Indri Purnamasari Dian; Hastuti Sri (SHS Web of Conferences)
Urban tourism, characterised by its diverse offerings and accessibility, has gained significant attention. Museums, as prominent cultural and experiential attractions, play a crucial role in shaping urban tourism experiences. This study investigates the relationship between accessibility and museum tourist satisfaction, focusing on understanding how accessibility influences visitor experiences. By analysing 1,000 data points from a user-generated content platform using linear regression, this research explores the impact of accessibility components, such as accessibility for people with disabilities and parking availability, on overall tourist satisfaction. The findings contribute to the growing knowledge of inclusive tourism and provide valuable insights for enhancing visitor experiences in urban museums.